2021
DOI: 10.2147/idr.s300814
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Treatment Outcome and Its Predictors Among Patients with Multidrug-Resistance Tuberculosis in Southern Ethiopia in 2014 to 2019: A Multi-Center Retrospective Follow-Up Study

Abstract: Background According to the 2017 global report, Ethiopia is among the top 30 high tuberculosis (TB) and multidrug-resistant tuberculosis (MDR-TB) burden countries. However, studies on MDR-TB treatment outcomes in Southern Ethiopia was very limited. Therefore, the study was aimed at determining the unfavorable treatment outcome and its predictors among patients with multidrug-resistant tuberculosis in Southern Ethiopia MDR-TB treatment centers. Subjects and Methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The current study found a 77.12% (95% CI = 73.0–81.5) MDR/RR-TB TSR, which is in agreement with the 75.7% national TSR report (from 2009 to 2019) by Habteyes Tola. 21 Other retrospective studies conducted in Addis Ababa (2011–2016) 26 and Southern-Ethiopia (2014–2019) 27 also reported similar findings, 76.9% and 76.32%, respectively. However, according to a review paper published in 2020, the overall pooled TSR in Ethiopia was 63.82%, which was less than the current report.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The current study found a 77.12% (95% CI = 73.0–81.5) MDR/RR-TB TSR, which is in agreement with the 75.7% national TSR report (from 2009 to 2019) by Habteyes Tola. 21 Other retrospective studies conducted in Addis Ababa (2011–2016) 26 and Southern-Ethiopia (2014–2019) 27 also reported similar findings, 76.9% and 76.32%, respectively. However, according to a review paper published in 2020, the overall pooled TSR in Ethiopia was 63.82%, which was less than the current report.…”
Section: Discussionsupporting
confidence: 52%
“…The mortality rate in the current study was 9.25% (95% CI = 6.2–12.3), which is in agreement with a report from Southern Ethiopia, 9.37%. 27 However, it was lower than other individual reports in Ethiopia. 22 , 28–31 The current result was even lower than death rates reported using nationwide data.…”
Section: Discussionmentioning
confidence: 68%
“…The degree of sputum AFB positivity or grading was assigned to one of the five categories (negative, scanty, 1+, 2+, and 3+). The sputum bacillary load was graded as negative when there were no tuberculosis bacilli per 100 field of observation, as scanty when there was one to nine bacilli per 100 field of observation, as plus one (1+) when there was 10–99 bacilli per 100 fields of observations, plus two (2+) when the observed bacilli were 1–10 per field, and three plus (3+) when the number of bacilli was greater than 10 per field of observation ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of MTB in sputum cultures was performed in Löwenstein–Jensen (LJ) solid medium and recorded as follows; no growth (none), record actual number (1–9 colonies), 1+ (10–100 colonies), 2+ (> 100–200 colonies), 3+ (> 200 colonies), positive for other mycobacteria (other mycobacterial growth), contaminated (contaminated), and positive for MTB and contamination ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as hospitalizations for care, male sex, and low hemoglobin level increased the risk of unfavorable treatment outcomes. 6 In a national TB service quality assessment across Ethiopia, the treatment success rate for DR-TB patients was 70%. Three percent of the patients failed DR-TB treatment and were moved to pre-XDR drug-resistant TB treatment; 10% died during treatment; and 11% were loss-to-follow-up (LTFU).…”
Section: Introductionmentioning
confidence: 99%